Forecasting property market dynamics: Insights from the property cycle indicator - Puah, Chin-Hong; Kuek, Tai Hock; Mohammad Affendy, Arip; Siew, Shirty Ling Wong (International Information Institute Ltd., 2016)
The present study replicates the movement of the property cycle in Malaysia and predicts the timing of significant changes in property market dynamics. Combining property-related variables and macroeconomic series, the property cycle indicator (PCI) was established in the same manner as the [1]. The constructed PCI consistently exhibits predictive ability and leading attributes of the Malaysian property market across the period of 1991-2013. The average lead time of 3.7 months makes the PCI a forward-looking means of predicting the near-term prospects of the evolving property market. In essence, the empirical finding demonstrates that the indicator-based approach offers a promising early signaling mechanism for property market forecasting